A novel hybrid thermal management approach towards high-voltage battery pack for electric vehicles. (1st November 2021) - Jin, Lu; Tian, Jun; Gao, Shen; Xie, Peng; Akbarzadeh, Mohsen; Kalogiannis, Theodoros; Berecibar, Maitane; Lan, Yuanliang; Hu, Daozhong; Ding, Yulong; Qiao, Geng
Highlights: A 35kWh battery pack with a novel hybrid thermal management system is prototyped. Phase change material is innovatively integrated with cooling plate. The battery thermal management at the battery pack level and module level is studied. Both cooling and thermal insulation performances are investigated. Desirable control strategies are obtained for battery pack under 0.5C to 1.5C discharge rates. Abstract: Controlling the temperature of a battery pack within an optimal range and ensuring uniform temperature distribution are the key to improving battery life. With the elevating energy density of batteries, more efficient and energy-saving thermal management system is urgently required for improving electric vehicle (EV) performance in terms of safety and long-term durability. In this work, a novel hybrid thermal management system towards a high-voltage battery pack for EVs is developed. Both passive and active components are integrated into the cooling plate to provide a synergistic function. A 35kWh battery pack incorporated with electrical, mechanical and thermal management components was designed, manufactured and integrated. As the core hardware, a pack-level cooling plate set was innovatively designed by integrating with phase change material (PCM). The results show that the combined passive and active cooling strategy ensured a desirable working temperature below 40˚C and a uniform heat distribution across the entire pack at discharging rates ranging from 0.5C to 1.5C under customized control strategies. Moreover, the cycling performance of air cooling and hybrid cooling, as well as the thermal insulation performance at both battery module level and pack level are compared, demonstrating the superior thermal management capability of the hybrid solution.